Khop Kupi Marketing Strategy In Attracting Consumers In Banda Aceh City - Utami, Ayu Riska; Amrusi, Amrusi; Anggraini, Irma; Mustofa, Achmad; Razak, A. (Journal of Economics Education and Entrepreneurship, 2023)
This study aims to determine the marketing strategy used by Kupi Khop in Banda Aceh City. The approach used is qualitative with data collection methods using interviews, observation, and documentation. Informants in this study are business owners, employees, and consumers. The results of the study can be concluded that the products sold in the form of drinks made from coffee and non-coffee basic ingredients have gone well. The menu provided by Kupi Khop is also very diverse. The price of each drink is determined taking into account the cost of raw materials. The location of Kupi Khop is very strategic and is easily accessible to consumers because it is in an urban area. Maximum promotion on Instagram social media accounts is very good even though the social media used by Kupi Khop is only Instagram, but Kupi Khop often takes part in coffee festivals. In placing employees in accordance with their respective fields, there are employees in the service department, employees in the kitchen, employees specifically making coffee, so this shows that the organizational structure of Kupi Khop is going well. Kupi Khop prioritizes comfort and cleanliness. The process strategy includes ordering, serving, and paying in cash. Based on the results of this study it can be concluded that Kupi Khop has used a good marketing strategy by implementing the 7p marketing mix.